An Analysis of the Average Catch Production of Skipjack Tuna (Katsuwonus pelamis) by Pole-and-Line Fishing Vessels Owned by PT. Radios Apirja Sorong - Samsul Bachri; Roger R. Tabalessy; Dwi Indah Widya Yanti (Lembaga Penelitian dan Pengabdian, Universitas Kristen Papua, 2025)
This study aimed to examine the implementation of skipjack tuna (Katsuwonus pelamis) and tuna fishing operations using the pole-and-line fishing method at PT. Radios Apirja, Sorong Regency, West Papua. The research employed a descriptive method, with data collected through field observations, interviews, and documentation during fishing activities. The observed variables included the stages of fishing operations, the use of live bait, fishing grounds, and the catch obtained. The results showed that the pole-and-line method is an effective and selective fishing gear for catching skipjack tuna and tuna. The success of fishing operations is strongly influenced by the availability of live bait, oceanographic conditions, and the skills of the crew in operating the fishing gear. The fishing grounds located around the waters of Misool and Waigeo possess high potential for pelagic fish resources, thereby supporting the productivity of fishing activities. In addition, the fishing operations conducted by PT. Radios Apirja contribute to the local economy through partnership programs established with fishing communities. Therefore, the use of pole-and-line fishing gear can serve as an alternative approach for sustainable fisheries management in the West Papua region.